The Discourse of Pluralism in Islam And Hinduism: A Critical Examination of The Qur'an and Vedas - Lalu, Fathoni Hidayat (JURNAL PENELITIAN KEISLAMAN, 2023)
The concept of pluralism has been present in Indonesia for a long time, but it is still rejected by many. This rejection is due to the fatwa issued by the Indonesian Ulema Council that prohibits pluralism. Well-known Da'i constantly repeat and propagate this fatwa. However, from a different perspective, diversity is a necessity and unique to Indonesia. Religious pluralism in Islamic studies is based on the commitment and loyalty of each religious believer to their respective religious teachings, without sacrificing the truth of their own religion for the sake of coexistence and tolerance. Similarly, Hinduism acknowledges that pluralism is an undeniable fact in socio-religious life, recognizing the plurality of humans and other living things. Therefore, in sociological studies, individuals are often used to refer to humans due to their unique characteristics that are not shared by others.